Teacher-Students’ Relationship in Teaching and Learning Reading through Alphabet Cube to Young Learners - Nostalgianti Citra Prystiananta (Linguistic, English Education and Art (LEEA) Journal, 2019)
The research aims at describing teacher’s process in building teacher-students relationship in teaching and learning reading through alphabet cube to 15 young learners 5-6 years old and a teacher as the sample at RA AL-Barokah Jenggawah. This is a descriptive-qualitative research with data collection through observation, interview and documentation. In building teacher-students relationship in teaching and learning reading through alphabet cube, building a sense of community within the classroom and creating consistent routines and procedures were the highest frequency among all with 95 % and 93 % implementation. On the contrary, the use of humor, create consequences for behavior together and show courtesy were the lowest implementation by the teacher with 30 % and 47 % implementation. Other components implemented by the teachers included giving attention, motivation, sense of togetherness, individual assistance, proximity, feedback and using praise indicated the average percentage implementation from 63%-89%. It can be concluded that most of the activities in thirteen components in building teacher-students relationship in teaching reading using alphabet cube to the students at RA Al-Barokah Jenggawah were implemented above fifteen percent by the teacher. Keywords: teacher-students relationship, teaching reading, alphabet cube, young learners